Cover Feature: Sintering‐Resistant Metal Catalysts Supported on Concave‐Convex Surface of TiO2 Nanoparticle Assemblies (ChemCatChem 16/2018). Issue 16 (30th August 2018) - Duriyasart, Farkfun; Irizawa, Akito; Hayashi, Kahoko; Ohtani, Masataka; Kobiro, Kazuya
Abstract : The Cover Feature shows sintering‐resistant metal catalysts supported on concave‐convex surface of titania nanoparticle assemblies. In their Communication, F. Duriyasart et al. demonstrate that the nano concave‐convex surface of TiO2 support obstructs the movement of catalyst metal nanoparticles as compared to that of a smooth surface support which allows easy movement of the nanoparticles. It was shown that such nanoscale concave‐convex support surfaces effectively prevent sintering of metal nanoparticles, affording and maintaining small‐sized metal nanoparticles which resulted in high catalytic activity. More information can be found in the Communication by F. Duriyasart et al. onpage 3392 in Issue 16, 2018 (DOI:10.1002/cctc.201800624 ).